IMPLEMENTASI MEDIA PEMBELAJARAN E-MODUL BERBASIS SCHOOLOGY UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI SUHU DAN KALOR - A. Halim; Nasrullah Nasrullah; Yusrizal Yusrizal; Suhrawardy Ilyas; Sri Rezeki (Postgraduate, University of Mataram, 2021)
This study aims to analyze the increase in understanding of the learning concepts of students in class XI, Senior High School 9 Banda Aceh after the application of schoology-based e-module media on temperature and heat material. This study uses a quasi-experimental design method with a pre-test and post-test control group design. The research sample was taken by purposive sampling which was then divided into experimental class and control class. Concept understanding data was collected from multiple choice objective test scores of pretest and post-test. The concept understanding data was then tested based on the t-test value. The results of the assessment of understanding the statistical concept can be seen that the test results using the t-test with a t-count of 6.302 which is greater than the t-table value of 1.671, so it can be concluded that there is a significant difference. Data analysis and hypothesis testing were carried out with the help of SPSS for Windows Version 20. The conclusion of this study showed that the application of schoology-based e-module media increased students' conceptual understanding compared to conventional models